Pengaruh Akses Layanan Keuangan Digital dan Inklusi Keuangan terhadap Kinerja Keuangan Coffee Shop di Kota Pangkalpinang - Suci Wulandari; Antonio Lisiadi; Muhammad Haikal Faran Fajri; Nizwan Zukhri (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
This study examines how access to digital financial services and the level of financial inclusion affect the financial performance of coffee shops operating in Pangkalpinang. Using a quantitative approach and data from 50 respondents, the results indicate that both variables have a positive and significant impact on business financial performance. The analysis shows that transaction digitalization and financial inclusion enhance efficiency, profitability, and the stability of small enterprises. These findings provide valuable insights for developing financial strategies in the MSME sector and suggest the need to improve digital financial literacy as well as to expand the use of digital financial services by business actors and relevant institutions. The study also recommends further research to broaden the variables and geographic scope to obtain more generalizable results.